Uma sequência didática sobre área e perímetro utilizando o banco de questões da OBMEP e o GeoGebra - Santos Neto, Júlio Augusto dos (Universidade Federal de São Carlos, 2018)
This work presents a didactic sequence with questions of geometry developed from a problem of the OBMEP’s Question Database using as support a dialogical text and the software GeoGebra. Based on Didactic Engineering has accessible language, animated characters and computational resources. It intends to be an alternative learning for the development the student autonomy and transforming the teacher like mediator of this one. The OBMEP question requires the calculation of the perimeter of a quadrilateral contained in an equilateral triangle. Resolution requires geometric underlying knowledge to the problem that must be explored by the activities. Another traditional problem is the calculation of the largest area possible for a constant perimeter figure. Fractions, algebra and quadratic function are associated with geometric problems contributing to a contextualized and interdisciplinary learning. The work was carried out with the first year of the course on Computer Networks Integrated to High School of the Federal Institute of Education, Science and Technology of São Paulo (IFSP), Catanduva campus, in the months of October and November of 2017.
A didactic sequence on area and perimeter using OBMEP's questions database and GeoGebra
Keywords: Geometria; Perímetro; Área; Engenharia didática; Texto dialógico; GeoGebra; Geometry; Perimeter; Dialogic Text; CIENCIAS EXATAS E DA TERRA::MATEMATICA